Utilization of Solid Fuel in Environmentally Friendly Alternative Energy Learning - Candra Arie Nugrahanto; Pipit Puspitasari; Rizqy Renafasih Alinra; Wahyu Hanaldi (Business Management, 2026)
The target for the development of New and Renewable Energy (NRE) in the National Energy General Plan continues to increase toward 2050. The limited availability of fossil energy resources and the growing environmental impacts of their use encourage the development of sustainable and environmentally friendly alternative energy sources that can also be integrated into learning activities. One potential renewable energy source that can be utilized in educational contexts is Solid Clumped Fuel (SCF). SCF is a solid fuel produced through the densification of biomass waste using a clumping method, resulting in a product with higher density, easier handling, and favorable combustion characteristics. This study aims to examine the potential of SCF as an environmentally friendly alternative energy source and as a learning medium for renewable energy education. The analysis focuses on the production process, physical characteristics, and energy properties of SCF. The raw materials used consist of biomass waste, namely rice husk and sawdust, which are processed through drying, grinding, mixing, compaction, and final drying stages. The parameters analyzed include moisture content, calorific value, and particle size analysis. The results indicate that SCF has a competitive calorific value compared to conventional solid fuels and produces relatively lower emissions. Therefore, SCF has strong potential as an environmentally friendly alternative energy source and as a contextual learning medium to enhance students’ understanding of renewable energy concepts and sustainable biomass waste utilization.